Hubungan Sikap Perawat dengan Pencegahan Kejadian Dekubitus di Ruang Rawat Inap Rumah Sakit Bhakti Asih Tangerang Tahun 2024 - Dian Ayu Agustina; Upi Farida; Pratiwi Cahya Wardhani; Nurdewi Sulymbona (Pusat Riset dan Inovasi Nasional, 2025)
Pressure ulcers are one of the common problems in hospitals including intensive care units. The impact of pressure ulcers is quite severe and can cause death. Prevention of pressure ulcers is an important thing that nurses can do. The obstacles felt by nurses in implementing pressure ulcer prevention can affect nurses' beliefs, so that they can affect nurses' intentions and attitudes in implementing prevention. The purpose of this study was to determine the Relationship between Nurses' Attitudes and Prevention of Pressure Ulcers in the Inpatient Room of Bhakti Asih Hospital, Tangerang in 2024. The research method was quantitative research with a Cross Sectional approach. The research sample was 41 nurses using a purposive sampling technique. The measurement instrument used the Nurses' Attitude questionnaire and Pressure Ulcer Prevention using the Braden Scale. Data were analyzed using the Spearman Rho test. The results of the study showed that the results of the Spearman Rank correlation test obtained a significance level of p-value = 0.005 so that it can be concluded that there is a relationship between Nurses' Attitudes and Prevention of Decubitus Incidence in the Inpatient Room of Bhakti Asih Hospital, Tangerang in 2024. The correlation coefficient in this study has a value of 0.434 which means that the relationship value of these two variables is strong and inversely related. So that the relationship between the two variables is unidirectional. Conclusion, there is a relationship between the Relationship between Nurses' Attitudes and Prevention of Decubitus Incidence in the Inpatient Room of Bhakti Asih Hospital, Tangerang in 2024.